Lung Function at 8 and 16 Years After Moderate-to-Late Preterm Birth: A Prospective Cohort Study - Thunqvist, Per; Gustafsson, Per M; Schultz, Erica S; Bellander, Tom; Berggren-Broström, Eva; Norman, Mikael; Wickman, Magnus; Melén, Erik; Hallberg, Jenny (Pediatrics (Evanston), 2016)
Knowledge regarding lung function after moderately preterm birth is limited. We therefore investigated lung function at early school age and adolescence among children born moderately preterm. Data were used from the Swedish prospective birth cohort BAMSE (Swedish abbreviation for Children, Allergy, Milieu, Stockholm, Epidemiology study; N = 4089), with a 4.8% prevalence of moderate to late preterm birth defined as a gestational age of 32 to 36 weeks. Participants underwent spirometry at ages 8 and 16 years, and impulse oscillometry additionally at age 16 years. In total, 2621 children (149 preterm and 2472 term) provided lung function data. At age 8 years, adjusted forced expiratory volume in 1 second was lower in preterm female subjects (-64 mL [95% confidence interval (CI): -118 to -10]) compared with term female subjects but not in preterm male subjects. At age 16 years, both genders in the preterm group demonstrated lower forced expiratory volume in 1 second (female subjects: -116 mL [95% CI: -212 to -20]; male subjects: -177 mL [95% CI: -329 to -25]) compared with the term group. For the preterm group, impulse oscillometry demonstrated higher adjusted resistance at 5 Hz (female subjects: 31.3 Pa·L(-1)·s(-1) [95% CI: 6.3 to 56.3]; male subjects: 34.9 Pa·L(-1)·s(-1) [95% CI: 12.0 to 57.7]) and frequency dependence of resistance (resistance at 5 and 20 Hz) for male subjects (20.9 Pa·L(-1)·s(-1) [95% CI: 9.8 to 31.9]) compared with the term group. Measures of airway function assessed in adolescence were reduced in children born moderate to late preterm, and no catch-up in lung function between ages 8 and 16 years was observed.